The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.21203/rs.3.rs-476555/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and predictors of anaemia among adolescents in India: An exploration from Understanding the Lives of Adolescents and Young Adults Survey

Abstract: Background Anaemia is a public health concern affecting both developed and developing countries with significant consequences for both human health as well as social and economic development. Unfortunately, the anaemia intervention program, such as the National Nutrition Anaemia Prophylaxis Programme, mostly targets infants, young children, pregnant and lactation women, and not adolescents. Therefore, this study tries to fill this gap, aimed to study the prevalence of anaemia and the associated factors among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…We found that the prevalence of anemia was 37.3%, which is lower than similar studies conducted in other parts of the country. [ 8 , 11 13 ] However, several other studies conducted among the general adolescent population in the country, especially in the rural areas show a wide variation in the prevalence of anemia. [ 5 , 6 , 16 , 22 , 23 ] Although there has been controversies regarding the cut-off used to define anemia,[ 24 ] and there are methodological differences in estimation exist, still anemia remains as a significant public health challenge despite the rolling of several sponsored programs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the prevalence of anemia was 37.3%, which is lower than similar studies conducted in other parts of the country. [ 8 , 11 13 ] However, several other studies conducted among the general adolescent population in the country, especially in the rural areas show a wide variation in the prevalence of anemia. [ 5 , 6 , 16 , 22 , 23 ] Although there has been controversies regarding the cut-off used to define anemia,[ 24 ] and there are methodological differences in estimation exist, still anemia remains as a significant public health challenge despite the rolling of several sponsored programs.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] Several studies have documented high prevalence of anemia among tribal adolescents. [ 8 , 11 13 ] Odisha is one among the top few states in the country with a large (23%) and highest varieties of tribal population. [ 14 ]…”
Section: Introductionmentioning
confidence: 99%